Circulating myeloid‐derived suppressor cells correlate with clinical outcome in Hodgkin Lymphoma patients treated up‐front with a risk‐adapted strategy. (7th November 2014) - Romano, Alessandra; Parrinello, Nunziatina Laura; Vetro, Calogero; Forte, Stefano; Chiarenza, Annalisa; Figuera, Amalia; Motta, Giovanna; Palumbo, Giuseppe Alberto; Ippolito, Massimo; Consoli, Ugo; Raimondo, Francesco Di
Summary In the attempt to find a peripheral blood biological marker that could mirror the dysregulated microenvironment of Hodgkin Lymphoma (HL), we analysed the amount of myeloid‐derived suppressor cells (MDSC), including the three main sub‐types (monocytic, granulocytic and CD34 + fraction). The absolute MDSC count was investigated in 60 consecutive newly diagnosed HL patients and correlated with clinical variables at diagnosis and outcome. Patients received standard‐of‐care chemotherapy with the exception of interim fluorodeoxyglucose positron emission tomography (PET‐2)‐positive patients, who were switched early to a salvage regimen. All MDSC subsets were increased in HL patients compared to normal subjects (P < 0·0001) and were higher in non‐responders. However, a strong prognostic significance was limited to immature (CD34+) MDSC. A cut‐off level of 0·0045 × 109/l for CD34+MDSC resulted in 89% (95% confidence interval [CI] 52–99%) sensitivity and 92% (95% CI 81–98%) specificity. The positive predictive value to predict progression‐free survival was 0·90 for PET‐2 and 0·98 for CD34+MDSC count; the negative predictive value was 0·57 for PET‐2 and 0·73 for CD34+MDSC. PFS was significantly shorter in patients with more than 0·0045 × 109 CD34+MDSC cells/l at diagnosis and/or PET‐2 positivity (P < 0·0001). In conclusion, all circulating MDSC subsets are increased in HL; CD34+MDSC predict short PFS, similarly to PET‐2 but with the advantage of being available at diagnosis.